Mengapa Generasi Z Bertahan? Peran Empathic Leadership dalam Menekan Turnover Pekerja Generasi Z - Emmanuella, Evelyn Joyce; Putri, Calista Nathania Rendra; Ferdinan, Refigo Syahdan; Ferdinan, Bernardus Aris (Faculty of Business and Economics Universitas Atma Jaya Yogyakarta, 2026)
This study aims to examine the spiral effect of incivility and its impact on Generation Z workers in Surabaya. The respondents of this study were 200 non-managerial workers who belonged to Generation Z. The location of the study was Surabaya. The data was distributed using Google Forms and processed using structural equation modeling (SEM) with the Smart Pls tool. The results of the study indicate that family incivility has a positive influence on workplace incivility, workplace incivility has a positive influence on turnover intention, workplace incivility mediates the influence of family incivility on turnover intention, and emphatic leadership moderates by weakening the positive effect of workplace incivility on turnover intention. The practical implications of this study are that organizations need to manage workplace incivility because this behavior is not only an internal office problem but can also originate from external problems (family). Organizations need to create training to build empathy, provide work-family counseling, and build a culture of mutual respect. Strict sanctions for violations can be one of the efforts to prevent the spiral effect of incivility and protect victims. Keywords: family incivility, workplace incivility, emphatic leadership, turnover intention. Penelitian ini memiliki tujuan untuk mengkaji efek spiral dari ketidaksopanan dan dampak yang ditimbulkan pada pekerja generasi Z di Kota Surabaya. Responden dari penelitian adalah 200 pekerja non managerial yang masuk dalam kategori generasi Z. Lokasi penelitian adalah Kota Surabaya. Data didistribusikan menggunakan google form dan diproses menggunakan struktural equation modelling (SEM) dengan alat Smart Pls. Hasil penelitian menyatakan bahwa family incivility memiliki pengaruh positif terhadap workplace incivility, workplace incivility memiliki pengaruh positif terhadap turnover intention, workplace incivility memediasi pengaruh family incivility terhadap turnover intention, dan emphatic leadership memoderasi dengan melemahkan efek positif workplace incivility terhadap turnover intention. Implikasi praktis dari penelitian ini adalah organisasi perlu mengelola workplace incivility karena perilaku ini bukan hanya masalah internal kantor, tetapi juga dapat bersumber dari masalah eksternal (keluarga). Organisasi perlu membuat pelatihan untuk membangun rasa empati, menyediakan konseling kerja-keluarga, dan membangun budaya saling menghormati. Sanksi tegas terhadap pelanggaran dapat menjadi salah satu upaya untuk mencegah efek spiral dari ketidaksopanan dan melindungi korban. Kata kunci: family incivility, workplace incivility, emphatic leadership, turnover intention.